2024
DOI: 10.1161/hypertensionaha.123.21755
|View full text |Cite
|
Sign up to set email alerts
|

Histone Modifications and Their Contributions to Hypertension

Atrayee Ray,
Cary Stelloh,
Yong Liu
et al.

Abstract: Essential hypertension, a multifaceted disorder, is a worldwide health problem. A complex network of genetic, epigenetic, physiological, and environmental components regulates blood pressure (BP), and any dysregulation of this network may result in hypertension. Growing evidence suggests a role for epigenetic factors in BP regulation. Any alterations in the expression or functions of these epigenetic regulators may dysregulate various determinants of BP, thereby promoting the development of hypertension. Histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Epigenetic modifications have also been implicated in the regulation of vascular function in hypertension ( 82 ). Changes in DNA methylation and histone modifications can alter the expression of genes involved in vascular smooth muscle contraction, endothelial function, and vascular remodeling, contributing to hypertension development ( 129 ). Future research should focus on elucidating the specific epigenetic changes associated with vascular function-dependent hypertension and developing targeted therapies to restore vascular function and reduce blood pressure.…”
Section: Epigenome Modifications In Hypertension: a Classification Ba...mentioning
confidence: 99%
“…Epigenetic modifications have also been implicated in the regulation of vascular function in hypertension ( 82 ). Changes in DNA methylation and histone modifications can alter the expression of genes involved in vascular smooth muscle contraction, endothelial function, and vascular remodeling, contributing to hypertension development ( 129 ). Future research should focus on elucidating the specific epigenetic changes associated with vascular function-dependent hypertension and developing targeted therapies to restore vascular function and reduce blood pressure.…”
Section: Epigenome Modifications In Hypertension: a Classification Ba...mentioning
confidence: 99%
“…However, the homoplasmic form, late onset and incomplete penetrance of EH observed in these Chinese families carrying the tRNA Glu mutations suggested that the m.A14693G and m.A14696G mutations were involved in the development of EH but may be insufficient to produce a clinical phenotype; hence, other factors such as nuclear genes (ADD1; ALDH1A3), 49,50 environmental components (air pollution), epigenetic modification (histone modification, DNA methylation) 51,52 and personal lifestyle (smoking or high salt intake) may contribute to EH expression in these two families. 53,54 In particular, mito-nuclear communication played a putative role in the pathogenesis of cardiovascular disease.…”
mentioning
confidence: 96%